Sexual maturation among school teenagers and implications for family life (2004)
There appears to be an observed progressive drop in the age of sexual maturation among Nigerian adolescents. There is also progressive urbanization, industrialization and diffusion of western values into the culture, especially in relation to sexual morals and behaviour. The extent to which these changes may affect the sexual maturation processes, and their implications for health and the adolescents’ family life education and counselling were studied. A cross-sectional evaluation of the age of the attainment of secondary sexual characteristics among secondary> school students in Ibadan North Local Government Area, using a questionnaire study instrument was undertaken. The results show that the mean ages have not changed much for the general population when compared with previous studies. The values ranged from 12.2 years for the rapid growth spurt to 15.4 years for the sexual awakening. Mean age of the menarche was 13.2 years, similar to existing data. However, the interval between the onset of platonic heterosexual interest and sexual awakening was 0.9 and 0.4 years intervals in the boys and girls respectively. The obvious implications of the later for adequate sexual health and family life education for the youths are discussed.